Probing the practicality of ethical school leadership amid socio-political and economic turmoil - Chingwanangwanana, Bernard; Kgari-Masondo, Maserole Christina (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study aims to probe the practicality of ethical school leadership amid socio-political and economic turmoil. This was necessitated by the collapse of the Zimbabwean economy in 2000 up until 2009 when they abandoned their currency due to hyperinflation. The downturn of the economy has not been abated to date, and education, together with other social services has been affected tremendously. The objective of this study is to find out the practicality of school leadership amid social, political, and economic turmoil, such as the one prevailing in Zimbabwe. Based on the findings, the study aims to suggest ways of dealing with ethical school leadership in such an environment. A qualitative study was conducted involving two primary and two secondary schools, where four school heads and sixteen teachers constituted the sample. Semi-structured interviews and focus group interviews were conducted. The findings indicated that school heads and teachers are finding it very difficult to practice ethical school leadership in the environment prevailing in Zimbabwe. This paper proposes that ethical leadership be promoted in these schools through engaging the 'reusable past' from their African Indigenous Knowledge and additionally applying a multi-dimensional and multi-sectoral intervention strategy to bring sustainable and practical change.